2000
DOI: 10.1021/ja990123n
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of the Local Electrostatic Environment of the Tyrosyl Radical in Mycobacterium tuberculosis Ribonucleotide Reductase Observed by High-Field Electron Paramagnetic Resonance

Abstract: Ribonucleotide reductase (RNR) is a radical enzyme that catalyzes de novo biosynthesis of deoxyribonucleotides. The catalytically required tyrosyl free radical in class I RNRs is produced in conjunction with a µ-oxo-bridged diferric center in protein R2, 35 Å away from the substrate-binding site in protein R1. High-field EPR at 285 GHz was applied to probe the environment of the tyrosyl radical in both native and reconstituted samples of protein R2-2 of class Ib RNR from Mycobacterium tuberculosis. Two distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…; Table S5) (16)(17)(18)(19)(20)(21). A similar g-tensor anisotropy effect would be expected for a hydroxylated Trp radical because the radical spin density is typically delocalized over the entire indole ring (22)(23)(24)(25)(26)(27).…”
Section: Resultsmentioning
confidence: 53%
“…; Table S5) (16)(17)(18)(19)(20)(21). A similar g-tensor anisotropy effect would be expected for a hydroxylated Trp radical because the radical spin density is typically delocalized over the entire indole ring (22)(23)(24)(25)(26)(27).…”
Section: Resultsmentioning
confidence: 53%
“…Table 1 summarizes g-tensors for tyrosyl radicals from different selected class I RNRs. It was shown theoretically and experimentally that the g x -value is sensitive to the electrostatic environment of the tyrosyl radical in particular to hydrogen bonds between the CϭO group of the tyrosyl radical and the protein environment (6,(52)(53)(54)(55)(56)(57). The g x -value of 2.00916 (5) obtained for the tyrosyl radical Tyr-105⅐ in R2F and R1E⅐R2F of S. typhimurium clearly belongs to the first type of tyrosyl radicals as in E. coli, which is not hydrogenbonded.…”
Section: Frozen Solution W-band Epr Ofmentioning
confidence: 97%
“…The tyrosyl radical in a second RNR, termed class Ib, which was found as the active aerobic enzyme in some bacteria, e.g., Mycobacterium tuberculosis, showed significantly different hf tensors of the b-protons of the tyrosyl side chain compared with the class Ia enzymes present in E. coli and mouse (Liu et al, 2000). Class Ib RNR has a very similar overall structure for R2 compared with class Ia from E. coli (Figure 1) or mouse, except for a greater distance between the tyrosyl radical and the diiron site.…”
Section: Structure and Protein Interactions Of The Tyrosyl Radical Inmentioning
confidence: 99%
“…However, in contrast to class Ia, class Ib lacks overall allosteric activity regulation (Eklund et al, 2001). The difference in hf tensors of the b-protons between class Ia and class Ib was attributed to geometrically different side-chain orientations (see Figure 3; Liu et al, 2000;Eklund et al, 2001;Lendzian, 2005) largely determined by protein constraints. Indeed, theoretical studies indicated that the side chain orientations of the tyrosyl radicals Y122…”
Section: Structure and Protein Interactions Of The Tyrosyl Radical Inmentioning
confidence: 99%
See 1 more Smart Citation